Hepatitis C virus (HCV) micro-elimination in the hospital setting: The results of the HCV Caserta hospital project. Issue 5 (May 2022) - Messina, Vincenzo; Pisaturo, Mariantonietta; Alessio, Loredana; Russo, Antonio; Tripaldelli, Elena; Petruzziello, Arnolfo; Annecchiarico, Angela; Romano, Maria Rosaria; Maggi, Paolo; Coppola, Nicola
Abstract: Background: In the present study we evaluated the efficacy of an innovative model of HCV micro-elimination in a hospital setting in an area of high HCV prevalence. Patients and metods: Between January and December 2019, a prospective, interventional study for a program of HCV case-finding and linkage-to-care was performed in S. Anna and S. Sebastiano hospital of Caserta, in Campania, a region in southern Italy. All adult patients who were admitted to the Caserta hospital in the study period and resulted positive for anti-HCV were included in the study. The outcomes evaluated were the number of subjects resulting HCV-RNA-positive, those linked-to-care and treated with a DAA and the subjects whose anti-HCV-status was unknown. Results: In the study period, 14, 396 subjects, admitted to the hospital for different reasons, were tested for anti-HCV: 529 (3.7%) subjects resulted positive for anti-HCV. Of the 529 anti-HCV-positive subjects, 10 died during hospitalization and 243 were already treated with a DAA. The remaining 276 subjects were contacted and agreed to be evaluated. Of these 276 subjects, 68 patients resulted HCV- RNA-negative and 194 HCV-RNA-positive and 180 of these were treated with a DAA according to the international guidelines. Discussion: A simple, rapid, inexpensive model of HCV micro-elimination in the hospital setting allowed us to find anti-HCV-positive subjects with unknown anti-HCV status or not linked to a clinical center.